Differences in chick feeding frequency between parental sex and morph combination in the Common guillemot Uria aalge - Holmøy, Marthe Johansen (UiT Norges arktiske universitet, 2019)
The Common guillemot (Uria aalge) is a monomorphic seabird who exhibits two colour morphs: a bridled and an unbridled. The aim of this study was to investigate which effect parental sex and morph had on the daily chick feeding frequency and during the chick-rearing period. To assess this, two fixed time-lapse cameras were used to document the chick feeding frequency for 27 Common guillemot families for 24 hours over a period of four weeks. The families were divided into two morph combination categories: mixed morph (n = 11) and same morph (n = 16). The results showed evidence of a diurnal chick feeding frequency among females and a nocturnal chick feeding among males. We also reported a strong trend of increased male contribution in chick feeding frequency after chicks turned 19 days old. There was no evidence for any daily differences in feeding frequency between the two morph combinations. However, there was statistical support for a higher feeding frequency among mixed morph pairs after the chicks turned 10 days of age. Our findings may indicate that there are some underlying mechanisms behind parental investment through chick provisioning for both parental sex and morph combination. In addition, future studies should include additional variables (e.g. parental stress-level, adult and chick diet, metrological data) in order to distinguish any possible underlying mechanisms. We suggest time-lapse cameras with short intervals to be a good method for long-term observational studies in a non-invasive way and it might be a good tool to highlight critical associations between the ongoing climate change, change in food resources, management and future breeding success of this species. Keywords: chick feeding frequency, colour dimorphism, common guillemot, Hornøya, parental investment, seabirds, time-lapse camera, Uria aalge.